With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Gender, sexuality and colonial modernities - Burton, Antoinette M. (Routledge research in gender and history, 1999)
Gender, Sexuality and Colonial Modernities considers the ways in which modernity was constructed, in all its incompleteness, through colonialism. Using a variety of archival resources and equally diverse methodologies, the authors trace modernity's unstable foundations in the slippages and ruptures of colonial gender and sexual politics. As a whole, the essays illustrate that modern colonial regimes are never self-evidently hegemonic, but are always in process - subject to disruption and contest - and never finally accomplished; and are therefore unfinished business.
Keywords: 1800-1899; approches et analyses; colonialisme; cours; discipline; europe; fem1000; féminisme décolonial; histoire; occident; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; époque moderne; études postcoloniales